Computer risk profiling system for FTMSK computer's lab / Yusaniah Yusof - Yusof, Yusaniah (Faculty of Computer and Mathematical Sciences, 2007)
Computer Risk Profiling System is a system that identify the computer risk control and to mitigate those risks. This system enables users to track record on computer risks and also the actions toward those risks. It is so crucial for users to identify those computer risks in order not only to mitigate but also find ways on how to avoid computer risks. The purposes of this research are to identify the requirement for Computer Risk Profiling System, to design the Computer Risk Profiling System and to develop the Computer Risk Profiling System. In order seek for the system requirements, interviews have been conducted with several FTMSK computers' lab assistant. The output for this research project will be the prototype for Computer Risk Profiling System which allows several functionalities for users. Those functions will be including the process of registering new computer, registering computer risk and computer error maintenance report record. As the consequences for this functionality, users will be able to keep track the numbers of repeated occurrences for one's computer's risk and this will lead to the activities of identifying ways to prevent or avoiding those risks. This profiling system will be the guidelines for other users on how to deal with computer risks and ease their jobs when dealing with computer's problems. As the expansion for this research, other researcher might come out with system which is not only profiled those risks but also let the system itself dealing with those problems.